2022
DOI: 10.21203/rs.3.rs-1633832/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surface Premelting and Melting of Colloidal Glasses

Abstract: The nature of liquid-to-glass transition is a major puzzle in science because little structural change causes drastic dynamic slowdown1. A similar challenge exists in glass-to-liquid transition, i.e. glass melting, but it has been poorly explored. In particular, the surface effects on glass are not well understood2, especially in melting3–6. Here, we assemble monolayer, bilayer and trilayer colloidal glasses composed of tunable attractive spheres by vapour deposition such that they are sufficiently stable to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Similar to ξ dyn which is determined in the presence of a frozen interface and which characterizes the properties of the bulk glass 30 , the formation of a surface glassy layer during surface melting also reflects the properties of the underlying bulk material. Very recently, we became aware of another colloidal study which also observed that static and dynamic properties saturate at different depths near the surface of a glass 41 . Because in this study the attraction mechanism is different from ours, this strongly supports the idea the formation of surface glassy layers is expected to be a common phenomenon near the surface of glassy materials.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to ξ dyn which is determined in the presence of a frozen interface and which characterizes the properties of the bulk glass 30 , the formation of a surface glassy layer during surface melting also reflects the properties of the underlying bulk material. Very recently, we became aware of another colloidal study which also observed that static and dynamic properties saturate at different depths near the surface of a glass 41 . Because in this study the attraction mechanism is different from ours, this strongly supports the idea the formation of surface glassy layers is expected to be a common phenomenon near the surface of glassy materials.…”
Section: Discussionmentioning
confidence: 99%